An Extensive Research on Optimization Algorithms and its Application on Task Scheduling in Cloud Computing - K.Priyadarsini, K.Malathi (International Journal of Advanced Science and Technology, 2020)
Generating access data today competes with lot of complexities for searching, storing, manipulating and retrieving. Cloud computing, for building large and complex infrastructure is suitable for huge and wide variety of metadata. On the nub for data storage and ciphering, cloud computing is contributing at maximum proportion. It is a system of various large virtual machines linked to each other performing several virtualization computations. Cloud computing is a method where application and server data storages are sent to the internet services. The arranging of data is done with the help of task scheduling in virtual machines (VMs). Based on the certain scheduling the system will allocate the task into suitable resources within a workflow. This creates a new level of availability, scalability and flexibility. Various tradition method has been applied to achieve a fast task scheduling in cloud. Here, we present an analyzed comparison table for optimized technology for scheduling the tasks into the various distributed virtual machines. Various algorithms with their applications will check the requirement of different algorithms on network reducing the burden on processors for task scheduling. By this comparison one can try to optimize the time, cost, and fuzziness as per need.Keywords: Cloud Computing, Virtual Machine, Optimized Algorithms, Task Scheduling, Applications, Comparison Table